The effect of flowable composite and mode of polymerization on the microleakage of class v composite resin restorations - Salvador, Anna Dominique M.
#aPolymerization shrinkage remains the biggest challenge in resin-based composite restorations. Polymerization shrinkage can bring about microleakage and eventual failure of the restoration. Soft-start polymerization and the use of flowable composite an initial layer have been suggested to address microleakage. A experiment on different technique combination of light curing and filling technique which may indicate what method is most ideal in reducing microleakage in composite restorations was performed. Methods: Forty-eight adult human posterior teeth were selected and prepared w/ uniform class V cavity preparations. The samples were randomly assigned to four groups and were restored with or without flowable composite; and w/ conventional or soft-start polymerization. The samples were subjected to a dye penetration test. Data was subjected to kruskal-Wallis Test. Results: Conventional light curing with and without flowable composite when compared to soft-start polymerizationb with and without flowable composite has no significant difference when it comess to reducing microleakage in Class V composite restorations. Conclusion: The use of flowable composite as an initial layer and varying modes of polymerization does not significantly reduce microleakage in Class V composite restoration when compared to conventional filling and light-curing techniques.